What motivates avid readers to maintain a regular reading habit in adulthood? - Merga, Margaret (Australian Literacy Educators' Association, 2017)
Regular engagement in recreational book reading remains beneficial beyond early childhood. While most of the research in reading motivation focuses on the early schooling years, regular recreational book reading remains a highly beneficial practice beyond childhood, as it continues to enhance literacy skills and may help to maintain cognitive stamina and health into old age. Understanding why some individuals are avid readers in adulthood can offer insight into how to foster greater frequency of reading through both early and later interventions. This paper reports on data collected in the 2015 International Study of Avid Book Readers, which posed the question ‘Why do you read books?’ in order to capture self-reported motivations for reading from an adult sample. Qualitative data collected from 1,022 adult participants are analysed in order to explore the diverse and often interrelated motivations of adult avid book readers. Recurring motivations included perspective-taking; knowledge; personal development; mental stimulation; habit, entertainment and pleasure; escapism and mental health; books as friends; imagination and creative inspiration; and, writing, language and vocabulary. Findings offer a greater understanding of reading preferences and motivation of adult avid book readers, highlighting multiple potential points of engagement for fostering positive attitudes toward recreational book reading across the lifetime.